2018
DOI: 10.4103/2045-9912.235124
|View full text |Cite
|
Sign up to set email alerts
|

Comparing remifentanil, magnesium sulfate, and dexmedetomidine for intraoperative hypotension and bleeding and postoperative recovery in endoscopic sinus surgery and tympanomastoidectomy

Abstract: The study aimed to compare remifentanil, magnesium sulfate, and dexmedetomidine for intraoperative hypotension, bleeding volume, and recovery time in endoscopic sinus surgery and tympanomastoidectomy (TM). A double-blind clinical trial enrolled the patients undergoing endoscopic nasal sinus surgery and TM at Amirkabir Hospital (Arak, Iran), who were randomly assigned into three groups dexmedetomidine (DEX), remifentanil (REM), and magnesium sulfate (MgSO4) to which we intravenously administered 1 μg/kg DEX, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…And then 4 studies were excluded by full-text review for they were performed in pediatric patients. At last, 10 RCTs were enrolled in further meta-analysis [14][15][16][17][18][19][20][21][22][23]. The identification procedure of these eligible articles is described in Fig 1. The enrolled studies were published from 2011 to 2018, and all of them were published in English.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…And then 4 studies were excluded by full-text review for they were performed in pediatric patients. At last, 10 RCTs were enrolled in further meta-analysis [14][15][16][17][18][19][20][21][22][23]. The identification procedure of these eligible articles is described in Fig 1. The enrolled studies were published from 2011 to 2018, and all of them were published in English.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of 663 patients were randomized to receive two drugs. In 10 included RCTs, 5 were researches about head and neck surgery [14][15][16][17][18], 3 were researches about spinal surgery [19][20][21], and the rest two trials were researches about pituitary adenoma surgery [22] and laparoscopic colorectal resection surgery [23]. All enrolled studies reported the hemodynamic parameters (MAP, HR), and 6 studies reported the evaluation of surgical field bleeding by using 6-point scale [14][15][16][17][18]22].…”
Section: Basic Characteristics Of Enrolled Studiesmentioning
confidence: 99%
See 3 more Smart Citations